2006
DOI: 10.1158/1535-7163.mct-06-0133
|View full text |Cite
|
Sign up to set email alerts
|

B cell translocation gene 1 contributes to antisense Bcl-2-mediated apoptosis in breast cancer cells

Abstract: The antiapoptotic protein Bcl-2 is overexpressed in a majority of breast cancers, and is associated with a diminished apoptotic response and resistance to various antitumor agents. Bcl-2 inhibition is currently being explored as a possible strategy for sensitizing breast cancer cells to standard chemotherapeutic agents. Antisense Bcl-2 oligonucleotides represent one method for blocking the antiapoptotic effects of Bcl-2. In this study, we show that antisense Bcl-2 efficiently blocks Bcl-2 expression, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…CA-IKK2 induced several proapoptotic genes in Ramos cells. BTG1 (B-cell translocation gene 1), a Bcl-2-regulated mediator of apoptosis in breast cancer cells, 43 PLAGL1, IFIH1, and RUNX3 are all considered tumor suppressors because of their apoptosis-inducing capacities. [44][45][46] BID, a BH3-only protein promoting cytochrome c release, had been connected to MYC-induced cell-death priming.…”
Section: Discussionmentioning
confidence: 99%
“…CA-IKK2 induced several proapoptotic genes in Ramos cells. BTG1 (B-cell translocation gene 1), a Bcl-2-regulated mediator of apoptosis in breast cancer cells, 43 PLAGL1, IFIH1, and RUNX3 are all considered tumor suppressors because of their apoptosis-inducing capacities. [44][45][46] BID, a BH3-only protein promoting cytochrome c release, had been connected to MYC-induced cell-death priming.…”
Section: Discussionmentioning
confidence: 99%
“…Human carbon catabolite repressor protein-associated factor 1 (hCAF-1) can form a hCAF-1/BTG1 complex [14], which is dependent on the phosphorylation of a putative p34CDC2/cyclin E and p34CDK2/cyclin A kinase site on BTG1 Ser-159 [15]. BTG1 is a Bcl-2-regulated mediator of apoptosis and contributes to antisense Bcl-2-mediated cytotoxic effects in breast cancer cells [16]. BTG1 enhanced homeobox B9-mediated transcription in transfected cells and mediated their antiproliferative function [17].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of the cytoprotective function of Bcl-2 and Bcl-xL and their overexpression in breast cancer highlighted the evidence of the efficiency of ODN targeting the apoptotic pathways to sensitize breast carcinoma cells to standard anticancer therapy [15,17]. An interesting finding of Nahta et al shed light on the potential contribution of the induction of BTG1 in the cytotoxicity mediated by antisense Bcl-2 on ER-positive MCF-7 and negative MDA-MB-231 breast cancer cells, suggesting BTG1 as a novel Bcl-2-regulated mediator of apoptosis in breast carcinoma cells, whose induction contributes to antisense Bcl-2-mediated cell death [18]. The in vitro and in vivo studies of the effects of transient Bcl-2 downregulation revealed the promising potential of using Bcl-2 antisense ODN as a combinatory treatment for breast cancer.…”
mentioning
confidence: 99%